2020
DOI: 10.1186/s41155-020-00163-8
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and damages of the use of touchscreen devices for the development and behavior of children under 5 years old—a systematic review

Abstract: Aim Several health organizations have been expressing concern about the amount of time children spend using electronic devices and about the benefits and damages of the use of touchscreen devices, such as smartphones or tablets, for the development and behavior of children under the age of 5. A systematic review was carried out in order to understand the impact of touchscreen device usage toward children’s development and behavior under the age of 5. Methods Using the PRISMA method, from a total of 6314 stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 25 publications
0
16
0
9
Order By: Relevance
“…Tablet use in the early years might have posited both benefits and risks in early childhood development, thus deserves empirical studies. Rocha and Nunes reviewed 11 studies and found that the damages were superior to the benefits, especially when screen time increased [2]. They have also underscored the difficulties in finding studies directed to the desired age and type of electronic device, which is a potential cause of bias.…”
Section: 1tablet Use and Early Childhood Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Tablet use in the early years might have posited both benefits and risks in early childhood development, thus deserves empirical studies. Rocha and Nunes reviewed 11 studies and found that the damages were superior to the benefits, especially when screen time increased [2]. They have also underscored the difficulties in finding studies directed to the desired age and type of electronic device, which is a potential cause of bias.…”
Section: 1tablet Use and Early Childhood Developmentmentioning
confidence: 99%
“…Since the early 2010s, tablet use has become increasingly prevalent in young children's daily life and has prompted substantial public concerns about its impact on children's brain development [17,18]. Most of the existing studies have reported survey and behavioral evidence [2,3], yet no neuroimaging evidence has been reported. This study was thus dedicated to filling this research gap by conducting the DCCS task with fNIRS to understand the impact of tablet use on EF.…”
Section: Neuroimaging Studies On Early Executive Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infants and young children are exposed to more technologies than before as they have more devices and apps readily available for their use, resulting in increased screen time and tablet use [ 1 ]. This phenomenon has worried public health organizations, parents, and scholars who are seriously concerned about the benefits and damages of tablet use in the early years (ages 0–5) [ 2 ]. So far, many studies have examined the impact of tablet use on young children’s brain development, but the results are still mixed [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tablet use in the early years might have posited both benefits and risks in early childhood development, thus deserves empirical studies. Rocha and Nunes reviewed 11 studies and found that the damages were superior to the benefits, especially when screen time increased [ 2 ]. They also underscored the difficulties in finding studies directed to the desired age and type of electronic device, which is a potential cause of bias.…”
Section: Introductionmentioning
confidence: 99%